The Role of Judges in Preventing Divorce Due to Domestic Violence: An Islamic Law Perspective (A Case Study at the South Jakarta Religious Court) - Alyatul Himmah; Muhamad Arief Al Hakim; Hendro Risbiyantoro (Sahaja: Journal Sharia and Humanities, 2025)
The escalating prevalence of divorce cases attributable to domestic violence (KDRT) in Indonesia underscores the critical need for effective judicial intervention. This study examines the multifaceted role of judges at the South Jakarta Religious Court in preventing divorce resulting from domestic violence, evaluates the alignment of judicial practices with Islamic legal principles, and identifies the mechanisms employed in resolving such cases. Employing a qualitative case study methodology, primary data were gathered through in-depth interviews with a mediator judge and direct observations of mediation and court proceedings, complemented by secondary data from Islamic jurisprudence literature and official court documentation. The findings reveal that judges function as both law enforcers and mediators, systematically identifying domestic violence through evidentiary assessment and witness testimonies, and facilitating mediation using caucus techniques that allow victims to communicate without coercion. This judicial role aligns with the Islamic principles of justice (al-‘adl) and the protection of life (hifz al-nafs) within the maqāsid al-sharī‘ah framework. Although complete reconciliation remains rare, partial mediation outcomes demonstrate significant value in reducing future conflict.